Penerapan Metode Bermain Peran (Role Playing) dalam Meningkatkan Keterampilan Sosial Dan Keterampilan Berbicara Pada Anak Kelas II SD : (Penelitian Tindakan Kelas di Kelas 2 MI Nahdiyah Desa Tanah Tinggi Kecamatan Tapung Hilir) - Nurwahyuni Nurwahyuni; Siti Khadijah (Pusat Riset dan Inovasi Nasional, 2025)
Learning in elementary schools plays an important role in developing children's social and speaking skills. However, many students have difficulty communicating effectively and interacting with peers. This study aims to analyze the application of the role-playing method in improving the social and speaking skills of grade II students at MI Nahdiyah, Tanah Tinggi Village, Tapung Hilir District. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles. Data collection techniques include observation, interviews, and documentation. Observations are made to observe changes in students' social behavior and speaking skills after the application of the role-playing method. The data obtained are analyzed descriptively qualitatively. The results of the study indicate that the role-playing method is effective in improving students' social and speaking skills. Children become more confident in communicating, are able to work together, and express their opinions better. Thus, this method can be an alternative to fun and interactive learning for elementary school students.